Analysis and evaluation of riparian vegetation and adjacent land uses in the Toila River micro-watershed, Matanzas river sub-watershed, Guatemala - Quevedo Corado, J.E. (2008)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica),2008